Optimisasi Layanan Penyewaan Mobil melalui Pengembangan Aplikasi Mobile Membangun Solusi Efisien dalam Industri Penyewaan Mobil - Alifya Nuraisyar Aglaia; Andi Sri Auliya Putri; Ainil Aswariah; Kurnia Prima Putra (CV. Sakura Digital Nusantara, 2023)
The car rental industry has grown rapidly in recent years. More and more people need rental cars for business trips, vacations, or daily necessities. However, with the development of this industry, it becomes a new challenge for us so that it becomes a new problem and difficulty in finding and ordering car rentals easily and efficiently. The purpose of this car rental application is to provide clear and detailed guidelines for the team in building a good and effective car rental application. By developing this car rental application, we hope to provide a better and more efficient experience for prospective car renters. We believe that by utilizing digital technology, car rental can be simpler, transparent and easily accessible to everyone.